KAPABILITAS PRAKTIS DOMAIN PERJALANAN WISATA BALI: APLIKASI PERJALANAN WISATA BERBASIS PONSEL CERDAS - Kusuma Negara, I Made; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2018)
Bali as a popular tourist destination has succeeded in searching list of the most desirable destinations in a virtual world. Variety of information backed by increasingly technological developments has put the smartphone in a strategic position as a tour and traveling tool. The existence of the smartphone is very helpful for users to get information and meet various needs quickly. Thus, it is important to examine the preferences of tourists on the use of smartphone as tour and travel tool to Bali. The concept of information technology on tour and travel as the approach of this article. Collecting data done by questionnaire method as much as 322 people of domestic tourists and foreign tourists who analyzed descriptively. The result of this research are the smartphone not only as a tool of technology alone, but has become a tourist travel tool as well as stage social activities, creativity, and share the experience. The shift in the stages of travel has changed due to the smartphone, tourists can choose to travel online, tourists can spontaneously change the travel plans due to unexpected events, and share a moment of the trip. The limitations of this article is the online information was not integral in facilitating the information needs of tourists.